1996
DOI: 10.1136/bjo.80.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of renin mRNA, angiotensinogen mRNA, and angiotensin converting enzyme mRNA expression in the human eye: evidence for an intraocular renin-angiotensin system.

Abstract: Aims/Background-All components necessary for the formation of angiotensin II, the biologically active product of the renin-angiotensin system (RAS) Since gene expression was highest in ocular parts, which are highly vascularised, local angiotensin II may be involved in blood supply and/or pathological vascular processes such as neovascularisation in diabetic retinopathy. (BrJ Ophthalmol 1996; 80: 159-163) The renin-angiotensin system (RAS) plays an important role in the control of blood pressure and electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
190
0
8

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(205 citation statements)
references
References 20 publications
7
190
0
8
Order By: Relevance
“…Over 2 years, lisinopril reduced the progression of DR by 50% (95% CI, 28-89%) and progression to proliferative DR by 80%. [41] This study concluded that ACE inhibitors may provide additional benefits in DR progression independent of BP lowering effect. [48] While the EUCLID study suggested beneÞ cial effects of ACE inhibitors, UKPDS [37][38][39] and the ABCD study could not confirm the superiority of ACE inhibitors over other antihypertensives.…”
Section: T a B L E 1 A M E R I C A N D I A B E T E S A S S O C I A mentioning
confidence: 71%
See 1 more Smart Citation
“…Over 2 years, lisinopril reduced the progression of DR by 50% (95% CI, 28-89%) and progression to proliferative DR by 80%. [41] This study concluded that ACE inhibitors may provide additional benefits in DR progression independent of BP lowering effect. [48] While the EUCLID study suggested beneÞ cial effects of ACE inhibitors, UKPDS [37][38][39] and the ABCD study could not confirm the superiority of ACE inhibitors over other antihypertensives.…”
Section: T a B L E 1 A M E R I C A N D I A B E T E S A S S O C I A mentioning
confidence: 71%
“…[39] Understanding the role of reninangiotensin system (RAS) in DR Preliminary studies have shown that angiotensin converting enzyme (ACE) is locally produced by endothelial cells of retinal vessels and retinal pigment cells. [40,41] The retinal ACE expression causes adverse changes in retinal blood ß ow and vascular structure. [42] A small clinical study also showed that subjects treated with ACE inhibitors had relatively lower levels of vitreous VEGF than those not on ACE inhibitor treatment [43] indicating that the adverse effects of retinal ACE expression may be mediated by potentiation of VEGF activity.…”
Section: T a B L E 1 A M E R I C A N D I A B E T E S A S S O C I A mentioning
confidence: 99%
“…The reninangiotensin system (RAS) has an important role in regulation of electrolyte balance, vasoconstriction, and vascular remodeling. Local renin-angiotensin regulation is present in the eye [139]. The role of the RAS in diabetic retinopathy has not been as well studied as that in the kidney and nephropathy; however, several studies including the Renin-Angiotensin System Study (RASS), Daily-Dose Consensus Interferon and Ribavirin: Efficacy of Combined Therapy (DIRECT) trial, and the ADVANCE Retinal Measurements (AdRem) have provided evidence that RAS inhibition may also be beneficial in diabetic retinopathy [140,141].…”
Section: Role Of the Renin-angiotensin System Its Inhibitors And Usmentioning
confidence: 99%
“…One such pathway is the renin-angiotensin system (RAS) as there is evidence that a local RAS including renin exists within the retina [2][3][4], and that prorenin is elevated in the plasma and vitreous humour of patients with proliferative diabetic retinopathy [5,6]. Furthermore, experimental studies indicate that ACE inhibition and type 1 angiotensin receptor blockade (ARB) are protective in models of retinopathy [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%